(RETRACTED) Yield of Sorghum bicolor (L.) Moenh Genotypes in A Plastic Mulch Planting System in Gunungkidul - muazam, Arif; Widyayanti, Setyorini; Daryono, Budi Setiadi (Jurnal Biodjati, 2023)
Sorghum is a strategic commodity with good nutritional and high antioxidant content that can be used as a source of food, feed, and industrial raw materials. Sorghum is a relatively low and less intensive crop than other staple food crops. Sorghum yield can be increased by establishing plant population through a mulching planting system. The purpose of this study was to determine the yield power of several sorghum genotypes, namely three new superior varieties (Bioguma, Kawali, and Samurai) and three local varieties (Plonco, Hitam Wareng, and Ketan Merah), planted with a plastic mulch planting system. The research was conducted on farmers’ land in Karangmojo, Gunungkidul, Daerah Istimewa Yogyakarta, which is a dryland soil type. The experimental design used a randomized complete block design (RCBD) with 5 replications. Observation parameters included growth components and sorghum production. The results showed that sorghum planting with a mulching planting system was able to provide yields for the Bioguma variety of 7.70 tons/ha, Plonco variety of 8.41 tons/ha, Samurai variety of 5.38 tons/ha, Kawali variety of 8.21 tons/ha, Hitam Wareng variety of 3.91 tons/ha, and Ketan Merah variety of 4.00 tons/ha. Based on the results of the study, it was found that the genotypes of local varieties were able to compete with new superior varieties and had the best growth response and yield power in the rainy season planting.